Pengaruh Identitas dan Ekuitas Brand J.CO Terhadap Keputusan Pembelian Konsumen - Amelda Pramezwary; Juliana Juliana; Charles Yap; Elvina Rosalie; Radella Terfinia (Kodepena Indonesia, 2020)
Abstrak Food and Beverage industry is one of industry that is very competitive within each businesses and brands. Every brand and business are using different strategies applied to gain customers based on their market segment and compete with competitors. The growing intensity of competition in the franchise business, such as J’CO, Dunkin Donuts, Krispy Kreme, Dough Darlings, and so on. Because of this, business owners must pay more attention to the desires of consumers who are diverse, change fast, and of course have different satisfaction values The object of this study was to learn the effect of the J.CO brand identity and brand equity on consumer purchasing. The sample consisted of 200 respondents who had answered a questionnaire about the J.CO brand and the marketing strategy undertaken by J.CO. Respondents were determined using accidental sampling technique. The purpose of this study was to determine the effect of brand identity and brand equity J.CO Donuts on consumer purchasing decisions. The samples that have been received are then analysed for their answers, starting with descriptive analysis, basic statistics, and regression. After this analysis, the results obtained in the form of J.CO’s brand identity have a significant effect, and the J.CO’s brand equity also has a significant effect. This shows that consumer purchasing decisions are influenced by brand identity and Equity Product. Keywords: Brand Identity; Equity Product; Consumer Purchasing Decisions